Exploration on Ideological and Political Teaching Path of Mental Health Education Course for Students in Private Colleges - Sun, Naixue; Ma, Hongmei (International Journal of Social Sciences and Public Administration, 2024)
This paper aims to explore the path of integrating ideological and political education into mental health education courses for students in private colleges, aiming to improve students' mental health and moral qualities. Firstly, by elaborating on the concept and importance of mental health education, the significance of mental health for the comprehensive development of individuals is revealed. Subsequently, through investigating and analyzing the mental health status of students in private colleges, some common mental health issues are identified, providing a basis for designing targeted educational courses. Secondly, addressing the characteristics and needs of students in private colleges, a comprehensive mental health education curriculum is designed, specifying the objectives, framework, content, and teaching methods to promote the comprehensive enhancement of students' mental health. In the exploration of the integration path of ideological and political education with mental health education, the inherent connection between ideological and political education and mental health education is discussed, and specific paths and strategies for integrating ideological and political education with mental health education are proposed. Finally, through the verification of practical cases, the effectiveness of curriculum design and implementation integrating ideological and political education is demonstrated, and prospects for future research directions are outlined, aiming to provide new ideas and effective measures for mental health education for students in private colleges.